Development of Nationalism Attitude in The Millenial Generation Through National Defense Education - Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2024)
This research aims to analyze the development of nationalist attitudes in the millennial generation through national defense education. The research method used in this research is the library method. The findings of this research are that to protect itself from destruction due to rapid technological developments and efforts to divide the nation, this nation must return to Pancasila, namely by building an attitude of nationalism through state defense education. National defense education is actually part of forming the identity and personality of the Indonesian people who are responsible, aware of their rights and obligations as citizens, love their country, so that they are able to display patriotic attitudes and behavior in the form of defending the country.